2023
DOI: 10.1021/jacs.3c09308
|View full text |Cite
|
Sign up to set email alerts
|

Control of One-Handed Helicity in Polyacetylenes: Impact of an Extremely Small Amount of Chiral Substituents

Tomoyuki Ikai,
Yuki Morita,
Tsuyoshi Majima
et al.

Abstract: Controlling the one-handed helicity in synthetic polymers is crucial for developing helical polymer-based advanced chiral materials. We now report that an extremely small amount of chiral biphenylylacetylene (BPA) monomers (ca. 0.3−0.5 mol %) allows complete control of the one-handed helicity throughout the polymer chains mostly composed of achiral BPAs. Chiral substituents introduced at the 2-position of the biphenyl units of BPA positioned in the vicinity of the polymer backbones contribute to a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…As shown in Figure S18E, inducement of chirality for the copolymers with rich aldehyde units was much more efficient than those with fewer aldehyde units, suggesting that the presence of more aldehyde moieties in the copolymers is helpful in forming more chiral imines with amino acid, together with the complexation between deprotonated amino acids and the copolymers, for an excess one-handed helicity induction. A recent paper reported that a small amount of chiral substituents (0.3 mol %) through covalent linkages were sufficient to amazingly control one-handed helicity for PPAs …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure S18E, inducement of chirality for the copolymers with rich aldehyde units was much more efficient than those with fewer aldehyde units, suggesting that the presence of more aldehyde moieties in the copolymers is helpful in forming more chiral imines with amino acid, together with the complexation between deprotonated amino acids and the copolymers, for an excess one-handed helicity induction. A recent paper reported that a small amount of chiral substituents (0.3 mol %) through covalent linkages were sufficient to amazingly control one-handed helicity for PPAs …”
Section: Results and Discussionmentioning
confidence: 99%
“…A recent paper reported that a small amount of chiral substituents (0.3 mol %) through covalent linkages were sufficient to amazingly control one-handed helicity for PPAs. 71 Chirality inducement of these copolymers was also examined through the addition of D-amino acids to the copolymer solutions with L-amino acids to verify the relationship between the chirality of the amino acids and the induced helicity from the copolymers. As shown in Figure 4A, with the addition of different equivalents of D-Phe, the first Cotton effect from copolymer PN 2.5 Ad 1 in the presence of 50 equiv of L-Phe changed accordingly.…”
Section: Dynamic Chirality Of Thementioning
confidence: 99%
“…Chiral transfer from molecular building blocks to supramolecular nanostructures through noncovalent interactions is an efficient approach for constructing supramolecular chiral materials. This phenomenon is also observed in living systems such as base pair, double stranded DNA, nucleic acid and even more complex structures. Design, fabrication and manipulation of supramolecular chiral nanostructures have attracted continuous attention due to their applications in asymmetric catalysis, disease treatment, sensing and display. Inspired by the chiral structures in biological systems, multiple noncovalent interactions such as hydrogen bonds, electrostatic attraction and van der Waals interactions are employed to construct artificial supramolecular chiral systems. π–π staking interaction, a type of attractive interaction, is prominent in aromatic groups containing π-conjugated segments which can be divided into three categories including edge-to-face (T-shaped), offset, and face-to-face stacked models. The binding energy values range from 1 to 50 kJ/mol . π–π stacking interactions have found numerous applications in crystal engineering, materials science and biochemistry. …”
Section: Introductionmentioning
confidence: 99%
“…Chiral or helical block copolymers not only inherit the structural features of conventional copolymers, but more interestingly, they can possess abundant morphologies due to involvement of chirality in their assembly. , Up to now, a variety of helical copolymers have been reported, including random copolymers, , block copolymers, and star copolymers. It was reported that by control of the backbone tacticity, assemblies from PPA block copolymers transform sequentially from vesicles to nanobelts and to helical strands . The screw sense of the helical strands was dominated by the helicity of the PPA block.…”
Section: Introductionmentioning
confidence: 99%